The feasibility of implementing advanced metering technology in high income areas in South Africa - Mwangi, Mburu (Water Research Group, 2017)
Water is an important natural resource and a building block to all life on earth. However, substantial increase in water demand and consumption has led to numerous nations, including South Africa, to face water scarcity. Improved water demand management strategies and water monitoring approaches are imperative. In South Africa, it's a legal requirement for all water supply points to be metered. Currently, water flow is primarily measured by conventional meters. However, substantial developments have been noted in the last two decades where conventional meters with added capabilities (such as communication capabilities) added have been introduced. These meters are known as advanced water meters. These capabilities offer functions such as leakage detection and more immediate consumption feedback. However, advanced meters also have significant disadvantages such as require high start-up capital and are susceptible to higher failure rates than conventional meters. It remains to be seen if advanced metering technology is an appropriate technology to be adopted in South Africa. Due to the different dynamics of South Africa's income level groups, the metering application and effects will differ for each income level group. Therefore, the purpose of this study is to investigate the feasibility of implementing advanced metering systems in high income areas in South Africa. An evaluation framework was developed to gauge the viability of implementing advanced metering systems on four performance criteria; technical, economic, environmental and social. The composite indicator framework template was selected as it was not tailor made for a specific reason and could be adapted for this research. The necessary framework input parameter data were acquired from practitioners in the field through questionnaires and from literature. Due to lack of advanced metering case studies in South Africa (except for prepaid meter), literature from developed countries were used as proxies. The input data entailed details of the current metering system, advanced metering system and new conventional metering system with the later used as a control for comparative purposes. The typical high-income scenario was derived from typical input data. For each input parameter, there were value ranges from the low parameter value to high parameter value. These ranges were used to conduct the sensitivity analysis on the framework to access critical input parameters to the success or failure of implementation Implementing advanced metering systems in high income areas in South Africa was found to be less economically viable than conventional meters. This is due to the lack of needed infrastructure for advanced metering as well as high initial capital costs and high operating costs. Advanced meters however proved to be more environmentally viable than conventional meters as they offered higher reduction in consumption. However, the manner in which faulty batteries are disposed could lead to environmental damage. Social factors were considered negligible for high income areas as revolts to introduction to new meters arises from financial constraints that those meters might induce. Further research with more South Africa based case studies and smaller scale advanced metering systems has been recommended.